Continuing the struggle for justice 100 years of the National Council on Crime and Delinquency - Krisberg, Barry; Marchionna, Susan; Baird, Christopher; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2007)
In October of 2006, NCCD will celebrate 100 years of excellence. This book is a collection of essays that represents the historical best of the NCCD Board and staff.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: National Council on Crime and Delinquency -- History; Criminal justice, Administration of -- United States; Electronic books